Exploring the Role of Tranexamic Acid in Dermatology: A literature Review - Górska, Aleksandra; Gniaź, Natalia; Grela, Wiktor; Niewiadomska, Jagoda; Furtak, Daria; Tulej, Dawid; Marko, Natalia; Dziedzic, Alicja; Marciniuk, Dominika; Głogowska, Paulina (Journal of Education, Health and Sport, 2025)
Introduction Tranexamic acid (TXA) is a synthetic plasmin inhibitor primarily used in treating bleeding disorders. However, its use in dermatology has gained increasing attention. Due to its anti-inflammatory properties and ability to inhibit tyrosinase activity, tranexamic acid has emerged as a promising agent for treating pigmentary disorders and inflammatory skin conditions. Purpose This review aims to identify and summarize the current applications of tranexamic acid in dermatology, including its mechanisms of action, effectiveness, and safety in treating common conditions such as melasma, hyperpigmentation, rosacea, psoriasis, angioedema, and in scar and discoloration therapies. State of Knowledge An analysis of the existing literature highlights the growing interest in TXA’s dermatological applications. Clinical studies suggest that tranexamic acid effectively reduces hyperpigmentation and mitigates inflammation in rosacea cases. However, several studies exhibit limitations related to sample size and methodology, underscoring the need for further, more detailed research. Conclusions Tranexamic acid shows promising therapeutic potential in dermatology, particularly for pigmentary and inflammatory disorders. However, further research is needed to fully understand the mechanisms of TXA and its therapeutic potential, which could lead to the development of novel treatment strategies in dermatology.